Global private-label convergence: Fact or fiction? - GIELENS, Katrijn (Institutional Knowledge at Singapore Management University, 2016)
This study considers a set of 67 countries to study whether PLs sharesconverge globally and if so to what long-run level PL shares in 60 product categoriesare expected to converge. The authors draw upon the economic convergenceliterature to establish an empirical specification that measures long-run PL sharedifferentials relative to a stabilized reference country. As such, they use the notionof β-convergence, taking place when countries with an initially lower PL level growfaster than countries already closer to a common steady state.